2020
DOI: 10.1088/2053-1591/ab608a
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and free vibration properties of clamshell particles/polyester composites

Abstract: In this work, an experimental investigation was implemented to identify the effect of adding clamshell powder (CSP) into the polyester matrix on the tensile and impact properties along with vibration characteristics of the particulate composites towards using eco-friendly reinforcement phase. Different weight ratios of clamshell powder, ranged from 0 to 20 wt%, were loaded into the polyester resin with particle sizes ranged from 25 to 75 μm. Tensile, Charpy impact and free vibration tests were performed to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…For example, the tensile strength of the polyamide 6.6 (PA 6.6)/maleated poly[styrene‐b‐(ethylene‐co‐butylene)‐b‐styrene] (SEBS) was reduced by addition of glass particles 29 . Hejna et al and Mostafa et al, 30,31 also found significantly negative trends in the mechanical properties of filled composites and concluded that the reason was the fact that no treatment was used for the fillers. Therefore, it is obvious that the particle/matrix interfacial adhesion has a noticeable effect on the strength of filled micro and nanocomposites.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the tensile strength of the polyamide 6.6 (PA 6.6)/maleated poly[styrene‐b‐(ethylene‐co‐butylene)‐b‐styrene] (SEBS) was reduced by addition of glass particles 29 . Hejna et al and Mostafa et al, 30,31 also found significantly negative trends in the mechanical properties of filled composites and concluded that the reason was the fact that no treatment was used for the fillers. Therefore, it is obvious that the particle/matrix interfacial adhesion has a noticeable effect on the strength of filled micro and nanocomposites.…”
Section: Resultsmentioning
confidence: 99%
“…The Charpy impact tester (Grund WP-400 testing machine) depend of a standard test section that will be broken with an oscillating hammer. The test section was performed according to ISO-179 standard it is supported at both edges so that the hammer hits it in the middle [16].…”
Section: Charpy Impact Testmentioning
confidence: 99%
“…A survey carried out among farmers and agricultural corporations in Egypt has expected that about 48.5 kg of palm residues is obtained per tree annually. 10,11 There is a proliferation of WPCs factories in the Middle East district. The proprietors of these industrial facilities need to increase the added value of this industry by increasing the loading of natural fibers used to reach more than twice the rate of plastic loading, but challenges are confronting us such as increased water absorption and a significant decrease in mechanical properties and the use of the coupling agent has become insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…A survey carried out among farmers and agricultural corporations in Egypt has expected that about 48.5 kg of palm residues is obtained per tree annually. 10,11…”
Section: Introductionmentioning
confidence: 99%